COVID-19 pandemic and biopolitics in Latin America - Waisbord, Silvio Ricardo (2021)
Given our longstanding interest in the datafied society in Latin America,we are interested in assessing the applicability in the region ofarguments about contemporary biopolitics in Europe and the UnitedStates. Even if it is early to draw categorical conclusions giventhat we are in the middle of the pandemic and its evolution andaftermath are unpredictable, there are indications that the currentsituation in the region does not match recent conclusions about the escalation of biopolitics. At the time of this writing, Latin America has become the new epicenterof the pandemic (Burki 2020) with growing number of reported cases ofinfections and deaths. Various governments in Latin America (Perú,Argentina, Bolivia, Chile, Ecuador, México, Colombia and Brasil) andthe Inter-American Development Bank have deployed digitaltechnologies to control the transmission of the virus and to supporttesting and tracing. They have collaborated with private companiesand universities in setting up mobile applications for geolocalizingand contact-tracing possibly infected people. Expectedly, theseactions have raised concerns about the negative impact of massivesurveillance.However,while we recognize the legitimacy of these concerns, the problem inLatin America takes different dimensions than in Europe, NorthAmerica, and East Asia. For the moment, the governments in the regionhave significant problems to launch and maintain massive digitalsurveillance apparatuses. What stands in the way of pandemic-drivenbiopolitics is not a firm official commitment to protecting personaldata or to balancing public health objectives and democratic rights.The obstacles are rather technological and institutional, namely,poor reach and limited effectiveness of digital and mobiletechnologies as well as deep-seated problems of state performance interms of governmentality and the provision of health services in theregion.